Partial substitution of chemical fertilizer by organic fertilizer benefits grain yield, water use efficiency, and economic return of summer maize - Zhai, Lichao; Wang, Zhanbiao; Zhai, Yuchao; Zhang, Lihua; Zheng, Mengjing; Yao, Haipo; Lv, Lihua; Shen, Haiping; Zhang, Jingting; Yao, Yanrong; Jia, Xiuling (Soil & tillage research, 2022)
Partial substitution of chemical fertilizer with organic fertilizer (PSCFOF) is being increasingly recognized as a promising approach for achieving sustainable agriculture. However, comprehensive evaluation of the effect of PSCFOF on the grain yield, water use efficiency (WUE), and its economic return of summer maize is lacking. In this study, field experiments examining the following five treatments were conducted over the 2019 and 2020 growing season: T1, application of chemical NPK fertilizer alone; and T2–T5, substitution of 15%, 30%, 45%, and 60%, respectively, of the chemical N rate of T1 with organic fertilizer. Compared with T1, the other treatments reduced the soil bulk density, and improved soil organic carbon content and the percentage of macro-aggregates (≥0.25 mm) in the 0–20 cm soil layer. The grain yield and WUE of T2 and T3 were significantly higher than that of T1, where as T1, T4 and T5 had similar effect. The higher grain yield and WUE under T2 and T3 treatments may related to its strong root system, higher soil water content, and elevated plant N uptake, which further improved the post-silking photosynthetic capacity, biomass production, and harvest index. The results of the economic benefit analysis indicated that, T2 and T3 increased the net benefit by 2257 and 1404 CNY ha-1, respectively, compared to T1. However, the net benefit was reduced under T4 and T5 treatments. In conclusion, by comparison with T1, T2 and T3 improved the grain yield, WUE, and economic benefit of summer maize. Although T2 can achieve the optimal economic benefits in a short-term, T3 may be a better choice from the perspective of long-term ecological and economic benefits, because of its greater potential to reduce chemical N fertilizer application rate. •PSCFOF at rates of 15% and 30% significantly increased yield and WUE.•PSCFOF increased yield and WUE by regulating soil properties, root growth and post-silking photosynthetic capacity.•PSCFOF at rates of 15% can achieve the maximum net benefit in short-term.•PSCFOF at rates of 30% would be a better choice from the perspective of long-term economic and ecological benefits.